DEVELOPING STUDENTS' DESCRIPTIVE READING SKILLS AND CRITICAL THINKING THROUGH THE SCAFFOLDING STRATEGY USING GOOGLE WORKSPACE FOR EDUCATION (GWE) - Umardani, Rudy; Saehu, Andang; Zuhairi, Aminudin (Jurnal Visi Ilmu Pendidikan, 2024)
The use of technology remains a need to integrate into the teaching-learning process. Meanwhile, the students are still weak in reading skills with their low critical thinking capacity and engage more activities not being tied and integrated into the learning process at school. The aim of this study was to explain the effectiveness of the scaffolding strategy using GWE on the students"™ descriptive reading skills and critical thinking and to inquire about the relationship between those two variables. This study used a quasi-experimental design with two research instruments, namely a standardized descriptive text test sourced from the National Examination from 2005-2019 and a 21-critical thinking questionnaire items that had been validated by the expert. The subjects of this research were the tenth grade of senior high students of an integrated public school in Tana Tidung and were taken randomly to be an experimental class and a control class with 32 students for each of these classes. The results revealed that the implementation of the scaffolding strategy with the use of GWE could develop the students"™ descriptive reading skills and critical thinking. Additionally, their descriptive reading skills and Greenstein"™s critical thinking across four dimensions, namely: (a) critical thinking, multiple viewpoints; (b) analysing information; (c) using data to develop critical insight; and (d) using data to develop advanced clarification indicated stronger relationship. Thus, the implementation of the scaffolding strategy had to be supported to develop in the teaching learning process and to research in a broader scope for continual development.